If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying b + 69 = -1b + 5 Reorder the terms: 69 + b = -1b + 5 Reorder the terms: 69 + b = 5 + -1b Solving 69 + b = 5 + -1b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add 'b' to each side of the equation. 69 + b + b = 5 + -1b + b Combine like terms: b + b = 2b 69 + 2b = 5 + -1b + b Combine like terms: -1b + b = 0 69 + 2b = 5 + 0 69 + 2b = 5 Add '-69' to each side of the equation. 69 + -69 + 2b = 5 + -69 Combine like terms: 69 + -69 = 0 0 + 2b = 5 + -69 2b = 5 + -69 Combine like terms: 5 + -69 = -64 2b = -64 Divide each side by '2'. b = -32 Simplifying b = -32
| 52+8x=12x+3 | | 3xy(x^2y^3z-2xy^4)= | | x(1-x)=1/4 | | 6/1-1/6 | | y-3+x+5=120 | | 18x=7x | | 5(t-5)=20 | | 2/5=5x2/2 | | (8x-2)(3x+2x-1)= | | 25-2(X+3)=X+7 | | (-4x)+y=11 | | 5x*-10=4x | | x^2-10x-30= | | -.8a-8=.2 | | -5c-10=10 | | 3c-8=17 | | (x^2-10x-30)/(x-5) | | 200=x(20-2x)(16-2x) | | 6x+4=20+4x | | 7(X-2)=3x-4 | | 18x+32=24x | | -a+-6a=-14 | | x-7+4=90 | | x-3=.99x | | 6+3(2x-1)=3x+12 | | 1x+1y=40 | | X+12=-2(x-3) | | 13x2/3 | | c/4-9=-5 | | 4(6n+3)-5=10 | | 3=12/r | | e^7x=430 |